Chemical mechanical polishing pad with uniform upright bubbles as well as preparation method and application of chemical mechanical polishing pad

By preparing a polishing layer of uniform upright cell cells in a chemical mechanical polishing pad, the problem of unstable polishing rate caused by the enlargement of cell cells is solved and the service life is extended.

CN119609960AActive Publication Date: 2025-03-14WANHUA CHEM GRP ELECTRONIC MATERIALS CO LTD
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202311173266.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-12
Publication Date
2025-03-14
Estimated Expiration
2043-09-12

AI Technical Summary

Technical Problem

During the polishing process of existing chemical mechanical polishing pads, the bubble cells will gradually increase over time, resulting in unstable polishing rate and affecting service life.

Method used

By adopting a preparation method, a coating slurry is prepared by dissolving the polyurethane resin, surfactant and black slurry in a solvent, uniformly coated on the support layer, and cured in a solidification bath to form a polishing layer with uniform upright bubble cells.

Benefits of technology

The polishing pad is achieved uniform pore diameter during the grinding process, stable polishing rate, and extend the service life of the polishing pad.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004444608930000061
    Figure BDA0004444608930000061
  • Figure BDA0004444608930000071
    Figure BDA0004444608930000071
  • Figure BDA0004444608930000101
    Figure BDA0004444608930000101
Patent Text Reader

Abstract

The invention provides a chemical mechanical polishing pad with uniform upright cells, a preparation method and application thereof. The preparation method comprises the following steps: a) dissolving polyurethane resin, a surfactant and black paste in a solvent to prepare coating slurry; b) uniformly coating the coating slurry on a supporting layer according to a certain thickness, and then immersing into a coagulating bath for curing and forming; and c) carrying out surface sanding on the washed and dried polishing layer, pressing grooves, and laminating a back adhesive layer and a release layer to obtain the chemical mechanical polishing pad. The chemical mechanical polishing pad prepared by the method has uniform upright bubbles, and compared with a traditional type of polishing pad, the polishing pad can be endowed with a more uniform polishing rate, and the service life of the polishing pad can be prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chemical mechanical polishing, and in particular to a chemical mechanical polishing pad with uniform upright pores, a preparation method and application thereof. Background Art

[0002] Chemical Mechanical Polishing (CMP) is a process that combines the grinding action of nano-particles with the chemical corrosion action of the polishing liquid to flatten the surface of the workpiece being polished on the polishing pad. Chemical Mechanical Polishing has been widely used in the flattening process of semiconductor wafers and is an essential process in the production of wafers used to manufacture electronic components.

[0003] As a key consumable in the chemical mechanical polishing process, chemical mechanical polishing pads use their unique pore structure to transmit polishing liquid and discharge reactants and waste generated during the polishing process. Among chemical mechanical polishing pads, soft polyurethane microporous polishing pads are usually used as finishing or final polishing to achieve a lower defect rate for polishing materials.

[0004] For soft polyurethane microporous polishing pads, most of the current research focuses on adjusting the pore structure in order to improve the polishing rate. For example, patent CN102029577A provides a polishing pad with a double-pore structure, which promotes high TEOS removal rate and high TEOS / Cu removal rate selectivity, as well as low defect rate; patent CN113524026A provides an offset porous polishing pad, which has a combination of large pores, medium-sized pores and small pores in the upper and lower sections of the horizontal offset to increase the compression rate of the polishing pad and the contact area of ​​the top polishing surface during the polishing process, thereby improving the polishing rate. Although the above patents can improve the polishing rate, as the polishing time increases, the surface of the polishing pad is continuously ground, the pores will gradually increase, and after reaching a certain level, the polishing rate will become unstable, affecting the service life of the polishing pad.

[0005] Therefore, further attempts and optimizations are still needed on the pore structure of the polishing layer to solve the problems existing in the prior art, improve the stability of the polishing rate and extend the service life of the polishing pad. Summary of the invention

[0006] In order to overcome the defects of the prior art, the present invention provides a method for preparing a chemical mechanical polishing pad with uniform upright pores. The polishing layer prepared by the method of the present invention has upright pores with uniform pore size. This form of pores can ensure that the pore size of the polishing pad is uniform during the grinding process, which helps to stabilize the polishing rate and also improve the service life of the polishing pad.

[0007] Another object of the present invention is to provide such a chemical mechanical polishing pad having uniform upright cells.

[0008] Another object of the present invention is to provide application of the chemical mechanical polishing pad having uniform upright cells.

[0009] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solution:

[0010] A method for preparing a chemical mechanical polishing pad having uniform upright cells comprises the following steps:

[0011] a) dissolving polyurethane resin, surfactant and black paste in a solvent to prepare a coating paste;

[0012] b) coating the coating slurry evenly on the support layer, and then immersing it in a coagulation bath for solidification; wherein the moisture content of the support layer is in the range of 10wt% to 30wt%; preferably, the support layer is made of a microfiber synthetic leather base fabric with a moisture content of 10wt% to 30wt% after immersion, drying and ironing;

[0013] c) The polishing layer after washing and drying is subjected to surface sanding, groove pressing, and bonding of a back adhesive layer and a release layer to obtain a chemical mechanical polishing pad.

[0014] In a specific embodiment, the polyurethane resin in step a) is a solvent-based polyurethane resin, and preferably, the 100% modulus of the solvent-based polyurethane resin is 4 to 11 MPa, preferably 5 to 7 MPa;

[0015] In a specific embodiment, the solvent is selected from any one of N,N-dimethylformamide, N,N-dimethylacetamide or N-methylpyrrolidone, preferably N,N-dimethylformamide.

[0016] In a specific embodiment, the surfactant in step a) is a non-ionic surfactant with a hydrophile-lipophile balance value of 10<HLB<15; preferably, the surfactant is a compound of one or more. For example, when two non-ionic surfactants A and B are selected, the HLB value after compounding is calculated by mass percentage:

[0017] HLB=HLB A *A%+HLB B *B%.

[0018] In a specific embodiment, the mass ratio of the polyurethane resin, the surfactant, the black paste and the solvent is 100:0.2-1.0:15-45:30-60, preferably 100:0.3-0.6:20-40:40-50.

[0019] In a specific embodiment, the slurry coating thickness in step b) is 1.80-2.00 mm, preferably 1.85-1.95 mm.

[0020] In a specific embodiment, the coagulation bath in step b) is a mixture of N,N-dimethylformamide and water; preferably, the mass ratio of N,N-dimethylformamide is 15% to 25%, preferably 17% to 22%.

[0021] In a specific embodiment, the temperature of the coagulation bath in step b) is 15-30° C., preferably 18-25° C.; the curing time in the coagulation bath is 30-50 min, preferably 35-45 min.

[0022] In a specific embodiment, in step c), the drying temperature is 60-100° C., preferably 70-80° C.; the drying time is 20-50 min, preferably 30-40 min.

[0023] On the other hand, a chemical mechanical polishing pad having uniform upright cells is prepared by the aforementioned preparation method, wherein the polishing layer of the chemical mechanical polishing pad has uniform upright cells in the vertical cross-sectional direction.

[0024] In another aspect, a chemical mechanical polishing pad having uniform upright cells obtained by the aforementioned preparation method or use of the aforementioned chemical mechanical polishing pad having uniform upright cells in chemical mechanical polishing.

[0025] Compared with the prior art, the chemical mechanical polishing pad prepared by the method of the present invention has the following beneficial effects:

[0026] 1) The preparation method of the present invention is relatively simple. The slurry is coated on a microfiber synthetic leather base fabric with a specific moisture content after being soaked, dried and ironed, and then solidified in a coagulation bath to form a polishing layer structure with uniform upright cells.

[0027] 2) The chemical mechanical polishing pad prepared by the method of the present invention can ensure that the pore size of the polishing pad is uniform during the grinding process, which is helpful to stabilize the polishing rate and also improve the service life of the polishing pad. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a scanning electron microscope spectrum of the polishing layer prepared in Example 1 of the present invention after washing and drying.

[0029] Figure 2 This is a scanning electron microscope spectrum of the polishing layer after washing and drying prepared in Comparative Example 1 of the present invention.

[0030] Figure 3 This is a scanning electron microscope spectrum of the polishing layer prepared in Comparative Example 2 of the present invention after washing and drying. DETAILED DESCRIPTION

[0031] In order to better understand the technical solution of the present invention, the following examples will further illustrate the method provided by the present invention, but the present invention is not limited to the listed examples, and should also include any other known changes within the scope of the claims of the present invention.

[0032] A method for preparing a chemical mechanical polishing pad having uniform upright cells comprises the following steps:

[0033] a) dissolving polyurethane resin, surfactant and black paste in a solvent to prepare a coating paste;

[0034] b) coating the coating slurry uniformly with a certain thickness on a support layer with a certain moisture content and then immersing it in a coagulation bath to solidify and form;

[0035] c) The polishing layer after washing and drying is subjected to surface sanding, groove pressing, and bonding of a back adhesive layer and a release layer to obtain a chemical mechanical polishing pad.

[0036] In step a), the polyurethane resin is a solvent-based polyurethane resin, preferably a wet-process polyurethane resin, which is a common synthetic leather resin, and the 100% modulus of the solvent-based polyurethane resin is 4 to 11 MPa, for example, including but not limited to 4 MPa, 5 MPa, 6 MPa, 7 MPa, 8 MPa, 9 MPa, 10 MPa, 11 MPa, preferably 5 to 7 MPa. Wherein, 100% modulus can also be referred to as 100% mold or 100% modulus, which have the same meaning in the present invention.

[0037] As the surfactant is a non-ionic surfactant with a hydrophile-lipophile balance value of 10<HLB<15, the type of surfactant can be one or more types of compound. When multiple types of compound are used, for example, when two non-ionic surfactants A and B are selected, the HLB value after compounding is calculated by mass percentage:

[0038] HLB=HLB A *A%+HLB B *B%

[0039] For example, Tween 65 (HLB = 10.5), Tween 85 (HLB = 11.0), Tween 20 (HLB = 13.3), PEG 400 (HLB = 13.1), etc., are converted into the HLB value after compounding according to the content of the nonionic surfactant as a coefficient. The amount of the nonionic surfactant added is 0.2-1.0% (based on the mass of the polyurethane resin), such as 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, etc., preferably 0.3-0.6%.

[0040] The solvent may be at least one selected from N,N-dimethylformamide, N,N-dimethylacetamide or N-methylpyrrolidone, preferably N,N-dimethylformamide.

[0041] The black slurry is a general black slurry used for coloring the polishing layer black. There is no particular limitation on the black slurry in the present invention, and the black slurry commonly used in the art can be used.

[0042] The mass ratio of the polyurethane resin, surfactant, black paste and solvent is 100:0.2-1.0:15-45:30-60, preferably 100:0.3-0.6:20-40:40-50, for example including but not limited to 100:0.2:15:30, 100:0.3:20:50, 100:1.0:45:60 and the like.

[0043] In step b), the uniform coating can be completely carried out by existing technology, and the present invention has no limitation. For example, coating is carried out by using a coater. The present invention only controls the coating thickness to be 1.8 to 2.0 mm, such as 1.8 mm, 1.85 mm, 1.9 mm, 2.0 mm, but is not limited thereto, and is preferably 1.85 to 1.95 mm.

[0044] As the support layer, a microfiber synthetic leather base fabric with a moisture content of 10-30% (mass fraction) after soaking, drying and ironing is selected, such as 10%, 15%, 20%, 25%, 30%, etc. The base fabric has no requirement on thickness, for example, it is usually 0.6-1.5mm.

[0045] The coagulation bath is a mixture of N,N-dimethylformamide and water, wherein the mass proportion of N,N-dimethylformamide is 15% to 25%, for example, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, etc., but not limited to these, preferably 7% to 10%.

[0046] The coagulation bath temperature is 15-30°C, for example, 15°C, 20°C, 25°C, 30°C, but not limited thereto, preferably 18-25°C; the curing time is 30-50min, for example, 30min, 35min, 40min, 45min, 50min, but not limited thereto, preferably 30-45min.

[0047] In step c), the drying temperature is 60-100°C, for example, 60°C, 70°C, 80°C, 90°C, 100°C, but not limited thereto, preferably 70-80°C; the drying time is 20-50 min, for example, 20 min, 30 min, 40 min, 50 min, but not limited thereto, preferably 30-40 min.

[0048] After the above drying step, a polishing layer is obtained, and the polishing layer is subjected to surface sanding, groove pressing and combined with a buffer layer by conventional processes in the prior art, and then a backing adhesive is attached, and a release layer is attached to obtain the chemical mechanical polishing pad with uniform upright cells of the present invention. These processes of surface sanding, groove pressing, backing adhesive layer attachment and release layer attachment are not particularly limited in the present invention, and can be referred to the prior art, which is well known to those skilled in the art.

[0049] The chemical mechanical polishing pad with uniform upright pores prepared by the method of the present invention can be applied to the field of chemical mechanical polishing, including but not limited to chemical mechanical polishing of silicon wafers, sapphires and the like.

[0050] The present invention is further explained below by more specific examples, but does not constitute any limitation.

[0051] The sources of the main raw materials used in the embodiments and comparative examples of the present invention are shown in Table 1:

[0052] Table 1. Sources of main raw materials in Examples and Comparative Examples

[0053]

[0054]

[0055] Unless otherwise specified, other raw materials or reagents were obtained from commercial sources.

[0056] Evaluation of moisture content of base fabric:

[0057] First, weigh the dry base fabric, immerse it in a water tank at room temperature for 30 minutes, take it out, dry it at 100℃, and then weigh it. The moisture content of the base fabric is:

[0058] W t =(m2-m1) / m1×100%

[0059] Where W t is the moisture content of the base fabric, m2 is the wet mass of the base fabric, and m1 is the dry mass of the base fabric.

[0060] Polishing layer evaluation parameters:

[0061] ① Polishing layer thickness: Use VEGA TS5136XM scanning electron microscope to observe the cross-sectional microstructure of the polishing layer, and use the software ruler provided in the scanning electron microscope to measure the polishing layer thickness.

[0062] ② Polishing layer hardness: Shore A hardness (test standard JIS K 6253) is used to determine the depth that can be measured by the indenter pressed against the surface of the test piece by a spring.

[0063] ③ Polishing test: Use E460 CMP testing machine for polishing experiment, use ANJI AEP U3061A polishing liquid, polishing pad diameter 609mm, copper target diameter 75mm.

[0064] The polishing parameters are as follows: polishing pressure 1.5 psi, polishing speed 50-60 rpm, polishing liquid flow rate 300 mL / min.

[0065] The film thickness was tested using an AMBioS XP-300 step profiler. The average value of the film thickness at 9 points was taken. The copper target removal rate was determined based on the difference before and after CMP.

[0066] Example 1

[0067] Preparation of the support layer: Immerse the microfiber synthetic leather base fabric in a water tank at room temperature for 30 minutes, take out the base fabric and squeeze out excess water, then dry and iron it at 100°C until the moisture content is 20%.

[0068] Preparation of polishing layer: 100 parts of solvent-based polyurethane resin①, 0.3 parts of Tween 65, 20 parts of black pulp, and 40 parts of N,N-dimethylformamide are prepared into polyurethane slurry, and the slurry is coated on the supporting layer with a thickness of 1.85 mm, and then immersed in a coagulation bath containing 22% N,N-dimethylformamide at 25°C for curing for 35 minutes. After washing with water, it is placed in a 70°C oven for drying for 30 minutes.

[0069] After the drying step, a polishing layer is obtained, and the polishing layer is subjected to surface sanding, groove pressing, and bonding of a back adhesive layer and a release layer by existing steps to obtain a chemical mechanical polishing pad.

[0070] The scanning electron microscopy spectrum of the prepared unsanded polished layer is shown in Figure 1 As shown, the polishing layer has uniform upright cells in the vertical direction of the cross section.

[0071] Example 2

[0072] Preparation of the support layer: Immerse the microfiber synthetic leather base fabric in a water tank at room temperature for 30 minutes, take out the base fabric and squeeze out excess water, then dry and iron it at 100°C until the moisture content is 10%.

[0073] Preparation of polishing layer: 100 parts of solvent-based polyurethane resin ②, 0.6 parts of Tween 85, 35 parts of black pulp, and 50 parts of N,N-dimethylformamide are prepared into polyurethane slurry, and the slurry is coated on the supporting layer with a thickness of 1.95 mm, and then immersed in a coagulation bath containing 25% N,N-dimethylformamide at 18°C ​​for curing for 45 minutes, and then washed with water and placed in an oven at 80°C for drying for 40 minutes.

[0074] After the drying step, a polishing layer is obtained, and the polishing layer is subjected to surface sanding, groove pressing, and bonding of a back adhesive layer and a release layer by existing steps to obtain a chemical mechanical polishing pad.

[0075] Example 3

[0076] Preparation of the support layer: Immerse the microfiber synthetic leather base fabric in a water tank at room temperature for 30 minutes, take out the base fabric to squeeze out excess water, and then dry and iron it at 100°C until the moisture content is 30%.

[0077] Preparation of polishing layer: 100 parts of solvent-based polyurethane resin ③, 0.2 parts of Tween 20, 45 parts of black pulp, and 60 parts of N, N-dimethylformamide are prepared into polyurethane slurry, and the slurry is coated on the supporting layer with a thickness of 2.0 mm, and then immersed in a 15°C coagulation bath containing 15% N, N-dimethylformamide for curing for 50 minutes, washed with water, and placed in a 100°C oven for drying for 50 minutes.

[0078] After the drying step, a polishing layer is obtained, and the polishing layer is subjected to surface sanding, groove pressing, and bonding of a back adhesive layer and a release layer by existing steps to obtain a chemical mechanical polishing pad.

[0079] Example 4

[0080] Preparation of the support layer: Immerse the microfiber synthetic leather base fabric in a water tank at room temperature for 30 minutes, take out the base fabric and squeeze out excess water, then dry and iron it at 100°C until the moisture content is 20%.

[0081] Preparation of polishing layer: 100 parts of solvent-based polyurethane resin①, 1.0 part of PEG400, 15 parts of black paste, and 30 parts of N,N-dimethylformamide are prepared into polyurethane slurry, and the slurry is coated on the supporting layer with a thickness of 1.8 mm, and then immersed in a coagulation bath containing 17% N,N-dimethylformamide at 30°C for curing for 30 minutes, and then washed with water and placed in a 60°C oven for drying for 20 minutes.

[0082] After the drying step, a polishing layer is obtained, and the polishing layer is subjected to surface sanding, groove pressing, and bonding of a back adhesive layer and a release layer by existing steps to obtain a chemical mechanical polishing pad.

[0083] Comparative Example 1

[0084] Preparation of support layer: The support layer was prepared by the same steps as in Example 1, except that the moisture content of the base fabric was 0.

[0085] Preparation of polishing layer: The same steps as in Example 1 were used to prepare the polishing layer.

[0086] After the drying step, a polishing layer is obtained, and the polishing layer is subjected to surface sanding, groove pressing, and bonding of a back adhesive layer and a release layer by existing steps to obtain a chemical mechanical polishing pad.

[0087] The scanning electron microscopy spectrum of the prepared unsanded polished layer is shown in Figure 2 As shown, the polishing layer has water drop-shaped bubbles in the vertical direction of the cross section, and the pore size is uneven and gradually increases from the upper part of the water drop hole to the lower part.

[0088] Comparative Example 2

[0089] Preparation of support layer: The support layer was prepared by the same steps as in Example 2, except that the moisture content of the base fabric was 40%.

[0090] Preparation of polishing layer: The same steps as in Example 2 were used to prepare the polishing layer.

[0091] After the drying step, a polishing layer is obtained, and the polishing layer is subjected to surface sanding, groove pressing, and bonding of a back adhesive layer and a release layer by existing steps to obtain a chemical mechanical polishing pad.

[0092] The scanning electron microscopy spectrum of the prepared unsanded polished layer is shown in Figure 3 As shown, the length of the water droplet holes in the polishing layer becomes shorter, and larger round bubbles are formed at the bottom.

[0093] The test results of the thickness and hardness of the polishing layers prepared in the examples and comparative examples are shown in Table 2.

[0094] Table 2. Polishing layer thickness and hardness test results

[0095]

[0096] The polishing pads prepared in the examples and comparative examples were subjected to polishing tests to obtain the variation of the polishing rate with the polishing time. The test results are shown in Table 3.

[0097] Table 3. Polishing rate versus polishing time

[0098]

[0099] It can be seen from the test results in Table 3 that the polishing pad prepared by the polishing layer prepared by the present invention has a stable polishing rate and a long service life.

[0100] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as limiting the present invention. Those skilled in the art will appreciate that, under the guidance of this specification, some modifications or adjustments may be made to the present invention. These modifications or adjustments should also be within the scope defined by the claims of the present invention.

Claims

1. A method for preparing a chemical mechanical polishing pad having uniform upright cells, characterized in that: The following steps are involved: a) dissolving polyurethane resin, surfactant and black paste in a solvent to prepare a coating paste; b) coating the coating slurry evenly on the support layer, and then immersing it in a coagulation bath for solidification; wherein the moisture content of the support layer is in the range of 10wt% to 30wt%; preferably, the support layer is made of a microfiber synthetic leather base fabric with a moisture content of 10wt% to 30wt% after immersion, drying and ironing; c) The polishing layer after washing and drying is subjected to surface sanding, groove pressing, and bonding of a back adhesive layer and a release layer to obtain a chemical mechanical polishing pad.

2. The preparation method according to claim 1, characterized in that: The polyurethane resin in step a) is a solvent-based polyurethane resin, preferably, the 100% modulus of the solvent-based polyurethane resin is 4 to 11 MPa, preferably 5 to 7 MPa; and / or The solvent is selected from any one of N,N-dimethylformamide, N,N-dimethylacetamide or N-methylpyrrolidone, preferably N,N-dimethylformamide.

3. The preparation method according to claim 1, characterized in that: The surfactant in step a) is a non-ionic surfactant with a hydrophile-lipophile balance value of 10<HLB<15; preferably, the surfactant is a combination of one or more surfactants.

4. The preparation method according to claim 1, characterized in that: In the step a), the mass ratio of the polyurethane resin, the surfactant, the black slurry and the solvent is 100:0.2-1.0:15-45:30-60, preferably 100:0.3-0.6:20-40:40-50.

5. The preparation method according to claim 1, characterized in that: The slurry coating thickness in step b) is 1.8 to 2.0 mm, preferably 1.85 to 1.95 mm.

6. The preparation method according to claim 1, characterized in that: In the step b), the coagulation bath is a mixture of N,N-dimethylformamide and water; preferably, the mass percentage of N,N-dimethylformamide is 15% to 25%, preferably 17% to 22%.

7. The preparation method according to claim 1, characterized in that: In step b), the coagulation bath temperature is 15-30° C., preferably 18-25° C.; the curing time in the coagulation bath is 30-50 min, preferably 35-45 min.

8. The preparation method according to claim 1, characterized in that: Step c) The drying temperature is 60-100° C., preferably 70-80° C.; the drying time is 20-50 min, preferably 30-40 min.

9. A chemical mechanical polishing pad having uniform upright cells obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the chemical mechanical polishing pad with uniform upright cells obtained by the preparation method according to any one of claims 1 to 8 or the chemical mechanical polishing pad with uniform upright cells according to claim 9 in chemical mechanical polishing.

Citation Information

Patent Citations

  • Dual-pore structure polishing pad

    CN102029577A

  • Offset pore poromeric polishing pad

    CN113524026A

  • Preparation method for green shallow-cured phenolic resin coated grinding tool

    CN102513943A

  • Chemical mechanical polishing pad capable of improving edge effect as well as preparation method and application of chemical mechanical polishing pad

    CN115816291A

  • Chemical mechanical polishing pad and preparation method and application thereof

    CN115946039A